2023
DOI: 10.1029/2022ja030565
|View full text |Cite
|
Sign up to set email alerts
|

Transient Response of Polar‐Cusp Ionosphere to an Interplanetary Shock

Abstract: Geomagnetic field and plasma convection on Earth are strongly affected by interplanetary (IP) shocks and solar wind dynamic pressure pulses [P dyn ] (e.g., Boudouridis et al., 2007;Yue et al., 2010). After the IP shock hits the magnetosphere, the magnetopause moves inward, toward the Earth and the eastward magnetopause current intensifies rapidly as a result of this prompt compression (Araki, 1994). In consequence, the horizontal component of the geomagnetic field in low and mid-latitudes typically responds wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The strengths of IP shocks are frequently determined by means of solar wind parameters such as the ratio of downstream to upstream plasma densities and shock Mach numbers (Andréeová & Pr˘ech, 2007;Lugaz et al, 2016;Tsurutani & Lin, 1985). When IP shocks strike the Earth's magnetosphere, many geomagnetic perturbations are observed in the magnetosphere-ionosphere (MI) system, including magnetic field perturbations in geosynchronous orbit (Villante & Piersanti, 2011;, ultra-low frequency wave activity (C.-R. Zong et al, 2009), satellite orbital drag (Krauss et al, 2018;, ionospheric disturbances (Belakhovsky et al, 2017;Liu et al, 2023), and sudden impulse signatures observed by ground magnetometers around the world (Chao & Lepping, 1974;Russell et al, 1994;Smith et al, 2020). Therefore, understanding IP shock geoeffectiveness is of paramount importance in space weather investigations (Alves et al, 2011;Echer et al, 2004;Su et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The strengths of IP shocks are frequently determined by means of solar wind parameters such as the ratio of downstream to upstream plasma densities and shock Mach numbers (Andréeová & Pr˘ech, 2007;Lugaz et al, 2016;Tsurutani & Lin, 1985). When IP shocks strike the Earth's magnetosphere, many geomagnetic perturbations are observed in the magnetosphere-ionosphere (MI) system, including magnetic field perturbations in geosynchronous orbit (Villante & Piersanti, 2011;, ultra-low frequency wave activity (C.-R. Zong et al, 2009), satellite orbital drag (Krauss et al, 2018;, ionospheric disturbances (Belakhovsky et al, 2017;Liu et al, 2023), and sudden impulse signatures observed by ground magnetometers around the world (Chao & Lepping, 1974;Russell et al, 1994;Smith et al, 2020). Therefore, understanding IP shock geoeffectiveness is of paramount importance in space weather investigations (Alves et al, 2011;Echer et al, 2004;Su et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Once generated, the TCVs propagate tailward away from local noon in the high‐latitude ionosphere with a speed of several km/s (Friis‐Christensen et al., 1988; Glassmeier et al., 1989; Lühr et al., 1996). The ionospheric flow vortices associated with TCVs have been observed by incoherent scatter radars (Lühr et al., 1996; Valladares et al., 1999) and Super Dual Auroral Radar Network (SuperDARN) radars (Kataoka et al., 2003; Liu et al., 2011, 2015, 2023; Lyatsky et al., 1999).…”
Section: Introductionmentioning
confidence: 99%